Dienogest Treatment Improves Quality of Life in Women with Endometriosis. Issue 4 (October 2015) - Luisi, Stefano; Parazzini, Fabio; Angioni, Stefano; Arena, Saverio; Berretta, Paolo; Candiani, Massimo; Cela, Vito; Fedele, Luigi; Litta, Pietro; Maiorana, Antonio; Nappi, Luigi; Porpora, Maria Grazia; et al.
Background: The aim of this study was to assess the efficacy of dienogest treatment in improving quality of life in women with endometriosis. Methods: This was a prospective observational multicenter study at the universities of Siena, Milano, Cagliari, Perugia, Busto Arstizio, Pisa, Padova, Palermo, Foggia, Roma, Pescara and Catanzaro, including 142 patients with a diagnosis of endometriosis who received dienogest 2 mg once daily, for up to 90 days. Each patient underwent an evaluation of pelvic pain measured by visual analogue scale (VAS) from 0 to 10 points, and of quality of life measured by a mental and physical index before and after treatment. Results: The mean ± SD of VAS was 8.2 ± 1.6 in women with endometriosis, and this progressively and significantly decreased to 5.9 ± 2.6 at the end of the study. Mental index score values increased from 39.0 ± 9.8 to 46.0 ± 9.1 (p<0.001); likewise, the physical index increased from 39.6 ± 9.6 to 47.7 ± 8.5 (p<0.001). During the treatment period, the most frequent adverse events (AEs) were headache (30.8%), followed by bleeding (29.4%), depression (26.6%), breast tenderness (23.8%) and acne (2.0%), but these were transitory, and none led to withdrawal from the study. Conclusions: The present prospective study showed that dienogest is an effective and well-tolerated treatment improving the quality of life in endometriotic women.